Comics artist versus artistic genius: Kverneland and Fiske’s approach to artists, metafiction, and allusion to contemporary sources in Kanon - Glötter, Laura (Comics and agency, 2022)
Das Kapitel Comics Artist versus Artistic Genius: Kverneland and Fiske’s Approach to Artists, Metafiction, and Allusion to Contemporary Sources in Kanon erschien in Comics and Agency auf Seite 119.
Gesehen am 10.04.2025